Effect of nerve mobilization with intermittent cervical segment traction on pain, range of motion, endurance, and disability of cervical radiculopathy - Yun, Young-Ho; Lee, Byoung-Kwon; Yi, Jae-Hoon; Seo, Dong-Kwon (Physical therapy rehabilitation science, 2020)
Objective: This study aimed to evaluate the effects of the Kaltenborn-Evjenth concept of nerve mobilization combined with intermittent cervical segment traction (ICST) on pain, Neck Disability Index (NDI) scores, range of motion (ROM) and endurance in persons with cervical radiculopathy (CR). Design: Two-group pretest-posttest design. Methods: Thirty subjects participated in this study and were randomly assigned to two groups. The ICST group (n=15) was performed simultaneously with nerve mobilization and cervical traction for the segment with cervical pain at the same time. The intermittent cervical total traction (ICTT) group (n=15) performed nerve mobilization and cervical traction for the whole cervical area at the same time. In this study, outcome measures such as the Visual Analog Scale (VAS), NDI, ROM, endurance (cranio-cervical flexion test), and passive intervertebral motion performed before and 4 weeks after the experiment were compared to investigate the effects of each intervention. Results: In both groups, there were significant differences in the VAS, NDI scores, and endurance, and there were significant differences between the two groups except for endurance (p<0.05). In the ICST group, significant differences were found in all ROM, and in the ICTT group, significant differences were found in only extension, and there were significant differences between the two groups (p<0.05). Conclusions: The ICST group showed more improvement than the ICTT group in pain, NDI scores and ROM. Moreover, our findings show that the ICST could be used as a new strategy for manual therapy in persons with CR. KCI Citation Count: 0